GENETIC AND ECOLOGICAL CHARACTERISTICS AN ORIGINAL VARIANT BORNE ENCEPHALITIS VIRUS (THE «GROUP 886»), CIRCULATING IN THE BAIKAL REGION - A. I. Paramonov; I. V. Kozlova; M. M. Verkhozina; Yu. P. Dzhioev; T. V. Demina; E. K. Doroschenko; O. V. Lisak; O. O. Fedulina (Acta Biomedica Scientifica, 2013)
New data was obtained about the original version of tickborne encephalitis virus (TBE), circulating in the territory of Eastern Siberia. With the help of molecular hybridization of nucleic acids (MGNA) and genome sequencing we revealed a group of 13 strains having a genetic structure analogous to strain 886-84, which was described earlier as the sole representative of the probable genotype 5. The formation of a separate cluster on the phylogenetic tree, differentiation level of genetic differences from other genotypes more than 12 %, own habitat, ecological relationship with all the links of a vector-borne chain, participation in human pathology, the stability and duration of circulation in nature confirms the validity of certification of «group 886» as a separate TBEV genotype 5.